High levels of IL-6 and IL-8 characterize early-on idiopathic pulmonary fibrosis acute exacerbations. (February 2018) - Papiris, Spyros A.; Tomos, Ioannis P.; Karakatsani, Anna; Spathis, Aris; Korbila, Ioanna; Analitis, Antonis; Kolilekas, Likurgos; Kagouridis, Konstantinos; Loukides, Stylianos; Karakitsos, Petros; Manali, Effrosyni D.
Highlights: Controversy exists about the pathogenesis of IPF-AEs. Early in the development of an IPF-AE, IL-6 and IL-8 blood levels are significantly increased. While TGF-β, IL-4, IL-10, and IL-13 levels show no difference compared stable IPF patients. Increased IL-6 and IL-8 levels are related to a higher risk of death in all IPF patients. Further studies are necessary to clarify the enigma of IPF-AEs etiopathogenesis. Abstract: Introduction: Controversy exists about the pathogenesis of idiopathic pulmonary fibrosis acute exacerbations (IPF-AEs). According to one hypothesis IPF-AEs represent the development of any etiology diffuse alveolar damage (DAD) upon usual interstitial pneumonia (UIP), whilst other researchers argue that an accelerated phase of the intrinsic fibrotic process of unknown etiology prevails, leading to ARDS. Different cytokines might be involved in both processes. The aim of this study was to assess pro-inflammatory and pro-fibrotic cytokines in the peripheral blood from stable and exacerbated IPF patients. Methods: Consecutive IPF patients referred to our department were included. Diagnoses of IPF and IPF-AE were based on international guidelines and consensus criteria. The interleukins (IL)-4, IL-6, IL-8, IL-10, and IL-13 as well as active transforming growth factor-beta (TGF-β) were measured in blood from both stable and exacerbated patients on the day of hospital admission for deterioration. Subjects were followed for 12 months. Mann-Whitney test as well as Tobit and logistic regression analyses were applied. Results: Among the 41 patients studied, 23 were stable, and 18 under exacerbation; of the latter, 12 patients survived. The IL-6 and IL-8 levels were significantly higher in exacerbated patients (p = 0.002 and p = 0.046, respectively). An increase in either IL-6 or IL-8 by 1 pg/ml increases the odds of death by 5.6% (p = 0.021) and 6.7% (p = 0.013), respectively, in all patients. No differences were detected for the other cytokines. Conclusion: High levels of IL-6 and IL-8 characterize early-on IPF-AEs and an increase in the levels of IL-6 and IL-8 associates with worse outcome in all patients. However, as the most representative pro-fibrotic cytokines, TGF-β, IL-10, IL-4 and IL-13 were not increased and given the dualistic nature, both pro-inflammatory and pro-fibrotic of IL-6 further studies are necessary to clarify the enigma of IPF-AEs etiopathogenesis.